Redimensionamento do controle judicial difuso de constitucionalidade no direito brasileiro - Abreu, Eduardo João Gabriel Fleck da Silva (2023)
This work aims to demonstrate the strengthening of the diffuse judicial control of constitutionality model in Brazilian law, which made it regain its relevance and status in the Brazilian legal system and rival the concentrated control model. The research was motivated by the news of the extinction, without judgment of merit, of the Declaratory Action on Constitutionality No. 18, considered to be prejudiced due to the decision rendered in Extraordinary Appeal No. 574.706. In this sense, we propose, as a research problem, to investigate what transformations the diffuse model has undergone in the constitutional and legal fields that have allowed it to restore its importance and place it on an equal footing with the concentrated control model. It is assumed that the creation of the Binding Summula and the General Repercussion have provided the diffuse judicial model with the ability to offer systemic results similar to those verified in the decisions taken in the scope of concentrated control proceedings, as well as, in the field of omissions, it is indicated the evolution of Supreme Court jurisprudence on the writ of injunction and the advent of Federal Law 13.300/2016 as factors strengthening the diffuse model. To enable a proper cognition of this subject and a thorough understanding of both consecrated models of judicial control, the first chapter discusses the emergence of each of them from their respective historical and legal contexts, so as to make it possible to understand the causes of the adoption of different models in different legal systems. From these bases, it becomes possible to understand, in the second chapter, the evolution of the Brazilian system of control of constitutionality, analyzing the causes of the shortcomings of the diffuse model that led to the implementation of the concentrated model and its growth, gaining the status of predominance. In this unfavorable panorama for the diffuse model, the third chapter addresses the constitutional and legal transformations that have transformed and revitalized the model. The project is based on exploratory research, based on the gathering of information and knowledge about the proposed subject by means of bibliographic research, that is to say, based on theoretical references that have already been prepared and published (such as books and scientific articles), as well as the study of judicial decisions, in order to analyze the object in its practical application. The technique used to collect data is the indirect documentation, through the use of bibliographic materials. A qualitative analysis of the data collected is carried out